McCartney : now and then [videorecording (DVD)] - McCartney, Paul; Donovan, 1946-; Martin, George, 1926-2016 (Trinity Creative Partnership, 2025)
Paul McCartney gained worldwide fame as the bass guitarist and singer for The Beatles. In this authorized documentary, Paul speaks candidly about his contribution to The Beatles, his relationship with John Lennon, and much more. With contributions from esteemed peers such as George Martin & Donovan amongst others, this documentary is a must-see for any fan of Paul McCartney and The Beatles.